Smell of Cuba Street : mapping smells to understand a place : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Cui, Tianyong (Massey University, 2019)
Smell has a great influence on how we know places and how we feel and it helps us to have a complete understanding of the outside world. This project focuses on the visual mapping of smell, which provides a new perspective to view and review a place. Taking the iconic Cuba Street in Wellington as the object of investigation, this research explores how audiences can obtain an experience of a place through its smell. The maps are designed as visual representations of smells, which inspires people to know a specific place from the perspective of smell.
Keywords: Odors; New Zealand; Wellington; Maps